COMPREHENSIVE REVIEW ON EFFECTIVE MEASURES EMPLOYED TO REDUCE INFANT INJURIES DURING DELIVERY. - 1Suyuf Ahmed Alwalah, 2Majdah Jalal Alruwaili, 3Fatimah HussienAlghamedi, 4Aeshah Saeed Mufakkir Almutairi, 5Mashael Ali Asmari, 6Faizah ShuwayhitAlruwaili, 7Lina Saeed Mufakkir Almutairi, 8Etra Mohammed Abdullah Alshehri (Chelonian Research Foundation, 2022)
This review gives an in-depth see of procedures to decrease infant child injury delivery and analyzes information, models, comes about, and discourse to assess their adequacy. This consideration highlights the significance of an evidence-based approach, counting doctors preparing, moving forward with demonstrative strategies, and therapeutic innovation. More critically, the discoveries highlight the imperative part of these practices in diminishing birth-related dangers. The proposals address the utilization of these measures in obstetric care. To extend security and make strides in results for infant children and moms. This comprehensive direction highlights the significance of preventative measures to address birth injury and give quality care back to infants and their families. Keywords: infant injuries, delivery, obstetrics, measures, healthcare, safety